2023
DOI: 10.1002/capr.12699
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative content analysis of ChatGPT's client simulation role‐play for practising counselling skills

Rakesh K. Maurya

Abstract: Role‐play is often used as a pedagogical technique by counsellor educators to help counsellors‐in‐training (CITs) learn and practise counselling skills. This study used qualitative content analysis to assess the effectiveness of Chat Generative Pre‐Trained Transformer (ChatGPT), an artificial intelligence (AI) chatbot, in simulating client role‐play to facilitate practising counselling skills. The author used 10 case vignettes to conduct a simulated role‐play where ChatGPT was asked to simulate the client and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The emergence of artificial intelligence may be one avenue that can support DP; recent research (Maurya, 2023) has demonstrated that ChatGPT, while not without some limitations, can play the role of a client quite well. Another possibility may be to use video stimuli as part of a wider DP regime, in which videos are practised in isolation prior to working directly with the supervisor, or before professional development workshops where a more procedural training based on repetition and feedback can be more closely observed and provided; this may also help with taking the shame out of learning and provide therapists with an initial feeling of safety, as described in Newman et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emergence of artificial intelligence may be one avenue that can support DP; recent research (Maurya, 2023) has demonstrated that ChatGPT, while not without some limitations, can play the role of a client quite well. Another possibility may be to use video stimuli as part of a wider DP regime, in which videos are practised in isolation prior to working directly with the supervisor, or before professional development workshops where a more procedural training based on repetition and feedback can be more closely observed and provided; this may also help with taking the shame out of learning and provide therapists with an initial feeling of safety, as described in Newman et al.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of artificial intelligence may be one avenue that can support DP; recent research (Maurya, 2023) How to cite this article: Mahon, D. (2024)…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [34] introduces RoleInteract, a tool to assess the sociality of role-playing conversational agents, bene ting both individual and group interactions. Additionally, Maurya [35] introduces ChatGPT as a simulated client for practicing counseling skills, with results indicating its authenticity, consistency, emotional expression, cultural sensitivity, empathy and self-awareness, enhancing the learning experience.…”
Section: Chatgpt and Role Playmentioning
confidence: 99%
“…Their direct and focused insights reflect a clarity of thought and understanding that is pivotal in educational discourse. According to Maurya [21], human responses are influenced by personal experiences, particularly in the context of memory and role-play conversations. This concise approach adopted by students holds value in various educational scenarios, providing clear and straightforward contributions to discussions.…”
Section: A Chatgpt's Versus Students' Perspectives On Interpersonal C...mentioning
confidence: 99%